Analisis Dampak Regulasi dan Kebijakan terhadap Pertumbuhan Green Sukuk dalam Portofolio Perbankan Syariah - Ihsan, Moh (Journal of Islamic Finance and Syariah Banking, 2025)
This study analyzes the relationship between Islamic financial regulatory policies and the growth of Green Sukuk instruments in Islamic banking portfolios. Using a qualitative descriptive approach through literature study, the research evaluates how existing regulatory frameworks affect the adoption and development of Green Sukuk as sustainable financing instruments within the Islamic banking system. The analysis results indicate that the implementation of policies supporting green investments, clarity of regulatory frameworks for sustainable financial instruments, and relevant fiscal incentives play significant roles in enhancing Green Sukuk portfolios in Islamic banking. This research contributes important insights for developing more effective policies to encourage sustainable financing through Islamic instruments